Gravity [videorecording (DVD)] - Cuarón, Alfonso; Cuarón, Alfonso; Bullock, Sandra; Clooney, George
Dr. Ryan Stone is a brilliant medical engineer on her first shuttle mission with veteran astronaut Matt Kowalsky. On a seemingly routine spacewalk, the shuttle is destroyed, leaving Stone and Kowalsky spiraling out into the blackness. The deafening silence tells them they have lost any link to Earth and any chance for rescue. As fear turns to panic, every gulp of air eats away at what little oxygen is left, and the only way home may be to go further out into the terrifying expanse of space.